The Role of Corporate, Legal and Macroeconomic Balance Sheet Indicators in Crisis Detection and Prevention - De la Rocha, Manuel (IMF Working Papers; Working Paper ;, 2002)
This study tests the recent balance sheet explanations of external crises in emerging market countries and the role of standards in these crises. Using several unique data sets, it finds that corporate sector balance sheets have a very significant impact on both the likelihood and depth of external crises. The indicators supplement, rather than substitute for traditional macroeconomic variables with standards playing potentially an important role. The results have implications for strategies to limit external vulnerability: they suggest that policymakers need to promote sound private sector financial structures, support sound shareholder rights, in addition to employing prudent macroeconomic policies to reduce exposure to crises. In sample predictions point to potentially large improvements in the predictive power of models that include these indicators.